How to Prepare Disaster Mitigation Knowledge for Prospective Teachers in Elementary School? - Eddy Noviana; Otang Kurniaman; Nugraheti Sismulyasih Sb; Sri Dewi Nirmala; Ratna Sari Dewi (AL-ISHLAH: Jurnal Pendidikan, 2021)
Knowledge of disaster mitigation is one of the must-have primary school teacher candidates. The research tries to identify the knowledge of prospective elementary school teachers about natural, non-natural, and social disaster mitigation. In this study, the teacher candidates referred to are primary school teacher of education department students at the University of Riau. The research method used is qualitative research. The research subjects were 69 elementary school teacher candidates. The data on disaster mitigation knowledge collected were: (a) definition of disaster mitigation; (b) type of disaster; and (c) disaster management procedures. The research instrument used was a list of interviews. Data collection using interview techniques, while data analysis using qualitative data analysis techniques. The results showed that the knowledge of prospective primary school teachers about the term disaster mitigation mainly stated that the notion of disaster mitigation is an effort to reduce or minimize the risk and impact of a disaster. The knowledge of prospective elementary school teachers about disasters has mentioned various types of natural and non-natural disasters. The knowledge of prospective school teachers in explaining disaster management procedures has provided answers about various disaster management procedures. The disaster management procedure that is most often referred to is flood disaster management. This study concludes that knowledge about disaster mitigation for prospective elementary school teachers is quite good.